The Influence of Nanoclay and Powdered Ceramic on the Mechanical Properties of Mortar - Noor R. Kadhim; Wail Asim M. Hussain; Abdulrasool Th. Abdulrasool; Mohammed A. Azeez (Civil Engineering Journal, 2022)
The amount of concrete utilized worldwide has lately grown due to rising populations and urbanization. The gas emissions during cement manufacturing and the usage of common resources result in a significant environmental threat. As a result, researchers are attempting to minimize the amount of cement consumed by using waste materials while lowering building costs. This research aims to minimize the amount of cement used in concrete by partially replacing it with ceramic powder waste while also increasing the mechanical qualities of concrete mortar by substituting cement with nanoclay hydrophilic bentonite. Mortar samples were prepared using five different replacement percentages of cement by nanoclay, including 0, 2, 4, 6, and 8%, and two replacement percentages of cement by ceramic powder, including 0% and 20%. Compressive and flexural strength tests were performed on mortar samples for 7, 14, and 28 days of moist curing. The toughness was also measured for all mixes by measuring the area under the load-deflection curve. Also, water absorption and relative densities for all mortar mixes were measured. The results show that replacing cement with 2% nanoclay and 20% ceramic powder increases the flexural strength by 11%. Doi: 10.28991/CEJ-2022-08-07-08 Full Text: PDF